Pengaruh Green Marketing dan Citra Merek terhadap Keputusan Pembelian Produk Le Minerale Kota Semarang - Anisa Tusyaidah; Saryadi Saryadi; Ngatno Ngatno (Universitas Diponegoro, 2023)
In the current era, consumers are more selective in making a purchase by considering several aspects, namely green marketing and the image of a product. Le Minerale is a brand of bottled drinking water that is well known to the public with a good reputation. However, based on sales data, it is known that sales of Le Minerale products experienced a relatively low increase compared to its competitor, the Club brand, with a difference of 27.5%. The purpose of this study was to determine the effect of green marketing and brand image on purchasing decisions for Le Minerale products in Semarang City. This research includes the type of explanatory research, taking samples through non-probability sampling techniques. Data was taken by distributing questionnaires directly to 96 respondents who were consumers of gallon-packaged Le Minerale products in Semarang City. The results of the study prove that the green marketing variable influences the purchasing decision of Le Minerale products, with a t value of 10.077 > 1.98525 (t table) and a sig value of 0.000. In the brand image variable, the results show that brand image has a significant effect on purchasing decisions for Le Minerale products, with a t value of 9.010> 1.98525 (t table). As well as green marketing and brand image have a significant effect on purchasing decisions, with a calculated f value of 70.954> 3.09 (F table). However, between the two variables, the green marketing variable has a greater effect than the brand image variable, which is equal to 51.9%. The suggestions that can be made by companies are carrying out activities with an environmentally friendly concept, educating about recycle points, increasing the distribution of information about the green marketing concept that is applied and incessantly introducing products and their advantages in various media so that they are easily recognized by the target market at large. Di era sekarang konsumen lebih selektif dalam melakukan suatu pembelian dengan mempertimbangkan beberapa aspek yaitu green marketing dan citra suatu produk. Le Minerale merupakan merek air minum dalam kemasan yang sudah banyak dikenal masyarakat dengan reputasi yang bagus. Namun, berdasarkan dari data penjualan, diketahui bahwa penjualan produk Le Minerale mengalami peningkatan yang cukup rendah dibandingkan kompetitornya yaitu merek Club dengan selisih sebesar 27,5%. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh green marketing dan citra merek terhadap keputusan pembelian produk Le Minerale di Kota Semarang. Penelitian ini termasuk tipe explanatory research, pengambilan sampel melalui teknik nonprobability sampling. Data diambil melalui penyebaran kuesioner secara langsung kepada 96 responden konsumen produk Le Minerale kemasan gallon di Kota Semarang. Hasil penelitian membuktikan bahwa variabel green marketing berpengaruh terhadap keputusan pembelian produk Le Minerale, dengan nilai t hitung 10,077>1,98525 (t tabel) dan nilai sig 0,000. Pada variabel citra merek, hasil menunjukan jika citra merek berpengaruh signifikan terhadap keputusan pembelian produk Le Minerale, dengan nilai t hitung 9,010>1,98525 (t tabel). Serta green marketing dan citra merek berpengaruh signifikan terhadap keputusan pembelian, dengan nilai f hitung 70,954>3,09 (F tabel). Namun, diantara kedua variabel, variabel green marketing berpengaruh lebih besar dibandingkan variabel citra merek, yaitu sebesar 51,9 %. Adapun saran yang bisa dilakukan oleh perusahaan yaitu melakukan kegiatan yang berkonsep ramah lingkungan, edukasi mengenai recycle point, meningkatkan penyaluran informasi mengenai konsep green marketing yang diterapkan serta gencarnya mengenalkan produk serta keunggulannya di berbagai media agar mudah dikenal oleh target pasar secara luas.